Regional approaches to the management of patients with advanced, radioactive iodine-refractory differentiated thyroid carcinoma. Issue 9 (September 2012) - Brose, Marcia S; Smit, Johannes; Capdevila, Jaume; Elisei, Rossella; Nutting, Christopher; Pitoia, Fabian; Robinson, Bruce; Schlumberger, Martin; Shong, Young Kee; Takami, Hiroshi
For patients with advanced, radioactive iodine-refractory differentiated thyroid cancer, current treatment guidelines recommend clinical trial enrollment or small-molecule kinase inhibitor therapy. However, details of patient management vary between countries depending on trial availability and national regulatory policies. Insufficient clinical trial data and variable disease characteristics challenge the creation of universal guidelines, and treatment plans often reflect regional influences. A multidisciplinary, multiregional panel of experts met to discuss regional approaches to managing patients with advanced, radioactive iodine-refractory differentiated thyroid cancer and the potential impact of emerging therapies on current treatment strategies. Despite process-oriented regional differences, the decision-making strategies were similar. Multidisciplinary teams used to manage high-risk patients varied in composition across regions, particularly regarding the responsible physician's specialty. Cytotoxic chemotherapy was viewed as limited in clinical benefit, and targeted agents as attractive, based on promising data. Panel members support clinical trial enrollment as the preferred treatment strategy for managing these patients.